Amor próprio e vazio infinito: uma análise do homem sem Deus em Blaise Pascal - Martins, Andrei Venturini (2011)
The main goal of this inquiry is to analyze the issue of human condition after the Adamic Fall, according to Blaise Pascal. We have chosen his Lettre that dates from October 17th, 1651, as our main object of analysis. This Lettre is anything but a marginal text within the author s work, representing, on the contrary, the debut of several meditations on themes such as death, compassion, providence, consolation, sacrifice, original sin, self-love, the infinite emptiness, the horror of death before and after the Fall, the love of live before and after the Fall. Our departing hypothesis is that, according to Blaise Pascal, man lives on attempting to deflect the infinite emptiness that dwell in him and fill it somehow, even though only Jesus Christ, as a mediator, is capable of fulfilling the void left by God. To sustain this hypothesis, two major concepts - that of self-love and that of infinite emptiness - present in the foresaid Lettre shall be analyzed throughout the two parts that form this research: A Theory of Original Sin and its Consequences and The Infinite Emptiness of man without God . In Part I, the focus is on the Jansenist spiritual direction of the XVIIth century, and its implications with regards to our object (First chapter). The second chapter focuses on the concepts of Self-Love and Infinite Emptiness, and there we raise the question whether, to Pascal, self-love as detachment from God is the root of all evil and all vices, and whether it is the cause of the infinite emptiness that dwells in man. Apart from Self-Love and Infinite Emptiness, the Lettre also mentions the will to domination and laziness as other consequences of the Adamic Fall. At the end of the first part (Third chapter), we intend to demonstrate the consequences of the Fall as Pascal puts them in the Écrits sur la Grâce: ignorance, concupiscence, guilt and eternal death. Thus, we shall have a more thorough perspective on the consequences of the Fall - something we shall name subjective collage , since we bring the Lettre near to the Écrits sur la Grâce and compose a picture with the consequences of the Fall. In Part II, titled The Infinite Emptiness of man without God , we have elaborated two chapters in order to meditate about human condition based on the concept of infinite emptiness. Chapter IV (the first in Part II) focuses on the relation between infinite emptiness and the Pascalian concept of divertissement; finally, the fifth and last chapter brings the concept of infinite emptiness near to that of Christ as Mediator